2019
DOI: 10.1590/0366-69132019653742582
|View full text |Cite
|
Sign up to set email alerts
|

Y3+ substituted Sr-hexaferrites: sol-gel synthesis, structural, magnetic and electrical characterization

Abstract: Y3+ substituted strontium hexaferrites having chemical composition SrYxFe12-xO19 (x= 0.0, 0.5, 1.0, 1.5) were successfully synthesized by sol-gel auto-combustion method. The structural and morphological studies of prepared samples were investigated by using X-ray diffraction technique, energy dispersive X-ray spectroscopy, field emission scanning electron microscopy (FE-SEM) and high-resolution transmission electron microscopy. The X-ray diffraction pattern confirmed the single-phase hexagonal structure of ytt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…[14,27] Unit cell volume for V 0.866a c = . [28] The decreasing value of cell volume from 47.599 to 47.567 Å 3 is attributed to the lattice parameters 'a' and 'c'. The distortion factor 'u' was computed by putting the lattice constants in the following relation: [29] 2…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…[14,27] Unit cell volume for V 0.866a c = . [28] The decreasing value of cell volume from 47.599 to 47.567 Å 3 is attributed to the lattice parameters 'a' and 'c'. The distortion factor 'u' was computed by putting the lattice constants in the following relation: [29] 2…”
Section: Resultsmentioning
confidence: 98%
“…The fractional reduction in distortion factor is analogues with the variation in lattice parameters. FWHM values of intensive peaks were considered for the evaluation of average crystallite size of the particles by using Debye-Scherrer equation: [28] avg B 0.9 t Cos…”
Section: Resultsmentioning
confidence: 99%
“…The other reason for a decrease in saturation magnetization in La substituted Ca hexaferrite as compared to Ni substituted Ca hexaferrite is that a substituted Ni is ferromagnetic material while La is a nonmagnetic material. Satpute et al [44] and Dahotre and Singh [45] observed that with non-magnetic material substitution the saturation magnetization decreases. Nandotaria et al [8] also reported a sharp decrease in saturation magnetization of Mg substituted M-type Sr-Cu hexaferrite nanoparticles, where Mg 2+ ion replaces Cu 2+ ion.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a way that can limit the search in the better regions to more accurate results is grid search. This approach was executed by searching and selecting the option with maximum correlation and minimum error in the present study to identify the optimal candidates in the following region 10 (16)…”
Section: Selection Of Model Optimal Parametersmentioning
confidence: 99%
“…It should be noted that such parameters describe the magnetic properties of the ferrites. [9][10][11][12][13][14][15] Clearly, discovering new properties and optimizing them is time and cost consuming and requires various research. As mentioned, the magnetic properties of ferrites are affected by parameters with complex interactions.…”
Section: Introductionmentioning
confidence: 99%